Inclusão escolar: desafios para a equipe gestora - Schramm, Cláudia Vieira (2021)
This work, inserted in Research Line 2 (LP2): Pedagogical Management and Educational Contexts, Professional Master's in Public Politic and Educational Management, was elaborated with the aim of knowing the administrative strategies of the management team to adapt the school to the legal requirements in the assistance to Special Education students. Research with qualitative exploratory approach having as participants, managers of a private school. Considering that inclusive education is a challenge that has been imposed on regular schools, it is up to the managers and their teams, in a joint effort, to update their institutional documents, so that, in this way, they offer an inclusive quality education, without causing the exclusion of the regular students. In conclusion, as the adjustments, both in the pedagogical and administrative sectors, impact the schools' financial sector, due to the necessary investments in new hires and in the physical space, it is understood that the inclusion process and its implementation are complex and involve the school as a whole, not only the Special Education sector and, thus, help the manager and management team to seek strategies that approach the fulfillment of the needs of the different professionals from the school who are involved in the inclusive process. As the final product was build a shared Matrix of Inclusive Strategies.